Pemanfaatan Daun Kelor (Moringa oleifera Lamk.) Sebagai Bahan Campuran Nugget Ikan Tongkol (Euthynnus affinis C.) - HASANAH, Hafidhah; , Dra. Titik Suryani, M.Sc (2015)
Moringa (Moringa oleifera Lamk.) contain active compounds and complete nutrition. The leaves are rich in vitamins A and C, beta-carotene in particular are used as a mixture of tuna fish nuggets. The purpose of this study was to determine levels of protein, water, beta-carotene and quality nuggets of tuna with the addition of moringa leaves. The research method using a completely randomized design (CRD) one factor, namely the formulation of swordfish and moringa leaves with 7 treatments, namely swordfish: Moringa leaves, A (80 gams: 20 g), B (70 g: 30 g), C ( 60 g: 40 g), D (50 g: 50 g), E (40 g: 60 g), F (30 g: 70 g) and G (20 g: 80 g) with 2 replications. The results showed that the highest protein content nugget found in treatment A (tuna 80 g: Moringa leaves 20 g) is 7.80%, the highest water content and beta-carotene found in treatments G (tuna 20 g: Moringa leaves 80 g) is 67.482% and 0.0161 mg / g and the best quality of tongkol fish nugget by adding kelor in sample D. Its shown by its color (dark geen), taste (salty enough), smell (rotten enough), tekstur (smooth enough) and acceptance of people (very good).